2018
DOI: 10.1002/sia.6600
|View full text |Cite
|
Sign up to set email alerts
|

Effects of plasma treatment of carbon fibers on interfacial properties of BMI resin composites

Abstract: High performance continuous fiber surface modification by inductively coupled RF plasma (ICP) and dielectric barrier discharge (DBD) low temperature plasma were conducted. X-ray photoelectron spectroscopy (XPS) and other analytical testing methods systematically studied plasma treatment time, discharge power, discharge pressure, etc, on fiber surface state, surface composition, and surface shape changes in the appearance and wetting properties. The results show that after plasma treatment the surface of the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Extensive research has been conducted on the physico‐chemical interaction between CFs and the matrix, [ 4–6 ] and a range of surface‐engineering methods have been studied with the aim to enhance CF/substrate interfacial strength, such as chemical/electrochemical oxidation, plasma treatment, polymer grafting, sizing and nanoparticle coating. [ 3,7–12 ] All these techniques aim to modify the surface morphology of CFs, to introduce new chemical groups to the CF surface, and to change the surface free energy and hence improve the CF/matrix interfacial bonding.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive research has been conducted on the physico‐chemical interaction between CFs and the matrix, [ 4–6 ] and a range of surface‐engineering methods have been studied with the aim to enhance CF/substrate interfacial strength, such as chemical/electrochemical oxidation, plasma treatment, polymer grafting, sizing and nanoparticle coating. [ 3,7–12 ] All these techniques aim to modify the surface morphology of CFs, to introduce new chemical groups to the CF surface, and to change the surface free energy and hence improve the CF/matrix interfacial bonding.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, the flax-alginate 100% DC sample experiences a more substantial increase in the C1s peak, which may be attributed to a degradation as suggested in the OES section. This degradation could be related to the conversion of carbon into CO 2 , leading to a significant decrease in the O/C ratio [47]. Additionally, a trend at 287.6 eV, associated with the C=O bond, suggests the presence or enhancement of carbonyl groups.…”
Section: Xpsmentioning
confidence: 99%
“…Treatment are therefore mainly devoted to cleaning the surface by removing the impurities, creating a surface roughness to improve the mechanical anchorage of the resin, or the chemical grafting on the fibre surface to create chemical interactions between the fibres and the matrix [42]. Thereby, as an example, some researchers have demonstrated that plasma treatment of carbon fibres allows the surface roughness of fibres to be increased and, consequently, enhances their adhesion with polymers [43][44][45]. Some others have carried out experimentations that aim at grafting chemical groups at the outmost surface of carbon fibres.…”
Section: Fluorination and Oxyfluorination Routesmentioning
confidence: 99%